STRATEGY FOR DEVELOPING ENTREPRENEURSHIP IN KAMPUNG PERCA DURING THE COVID-19 PANDEMIC - Daulat Marulitua Tambunan; Ferdinand Iskandar (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The existence of Kampung Perca Bogor is not only a center for marketing handicrafts, but also offers a shopping experience and educational tourism. The development of handicraft products is carried out by encouraging Kampung Perca to become a center for handicraft production and is also supported by a gallery as a local work facility. It is expected to improve the economy of the local community and expand the marketing of their products. Handicraft production using used cloth as the main raw material is an attraction for educational tourism of recycled products. This study uses a qualitative descriptive approach. Qualitative descriptive methods can be interpreted as problem-solving procedures that are investigated by describing or depicting the state of the subject or object of research (people, institutions and society) at the present time based on the facts that appear and as they are (Nawawi, 2005). This study intends to understand the phenomenon of what is experienced by the subject holistically and by means of description in the form of words and language, and by using various scientific methods. The basis of this research is expected to be able to provide a clear, detailed and scientific picture. Community education is education and learning that is rooted in the process of empowerment, social justice, the process of change, challenges, appreciation, and collective awareness. The development of community entrepreneurship is expected to be a new breakthrough in order to accelerate the achievement of the growth of independent entrepreneurs who have innovative, resilient and global-minded characters. This makes Kampung Perca Bogor present as a place that not only focuses on improving the community's economy but also focuses on other values,